Spectral analysis of aegelin isolated from maja leaves (Aegle marmelos Corr.) - Sugeng Riyanto (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
Aegelin is an alkaloid which isolated from Maja (Aegle marmelos Corr.) leaves. The molecular structure of the compound contains a chiral carbon atom. In our earlier publications the existence and influence of a chiral carbon atom have not been discussed yet. The existing of the chiral carbon atom gave rise two pair of doublets at d 3.67 J=3.4 Hz and d 3.43 J=8.5 Hz in the proton nmr spectrum. The doublets are signal of two proton which attached on adjacent atom of the chiral carbon atom which is confirmed bythe two dimension nmr spectrum (HMQC). The two protons are magnetic unequivalent which cause their chemical shifts are different. The protons appear as two doublet with different J value because its couple to a proton attached at the chiral carbon atom and the spin-spin splitting is observed. The existence of the two pairs of the doublets at d 3.67 d,J=3.4 Hz and d 3.42 d,J=8.5 Hz because the isolated aegelin from E.marmelos leaves contains of its enantimeer.Key words: E. marmelos, aegelin, enantiomeer, spectroscopy